Base-catalyzed addition of silylacetylenes to ketones: a route to protected tertiary propargyl alcohols - Kuciński, Krzysztof; Łuczak, Alicja; Mankouski, Aliaksei; Hreczycho, Grzegorz (The Royal Society of Chemistry, 2023)
The base-catalyzed addition of alkynylsilanes to ketone derivatives enables the formation of various silyl-protected propargylic alcohols. Commercially available and inexpensive potassium bis(trimethylsilyl)amide (KHMDS) serves as an efficient transition metal-free catalyst and permits the functionalization of a variety of derivatives, including pharmaceuticals and biorelevant compounds. Overall, the presented system complements classical routes to protected tertiary propargylic alcohols that mainly rely on stoichiometric processes or fluoride-mediated reactions.
This is the Accepted Version of the following article: Krzysztof Kuciński, Alicja Łuczak, Aliaksei Mankouski, Grzegorz Hreczycho, Base-catalyzed addition of silylacetylenes to ketones: a route to protected tertiary propargyl alcohols, Organic Chemistry Frontiers, 2023, 10, 2752-2759, DOI: 10.1039/D3QO00579H, which has been published at https://pubs.rsc.org/en/content/articlelanding/2023/qo/d3qo00579h#!divAbstract. In accordance with the RSC's publishing policy and the fact that the above-mentioned article has already been published via open access, the author of the manuscript has the right to publish the Author Accepted Manuscript version in an open repository.